Thinking, Photographing: A Place-based Approach in Practice-led Research - Hill, Rodrigo (Revista GEMInIS, 2022)
The article introduces photography practice as a practice-led research methodology, highlighting photographic conventions and methods as key research approaches. To illustrate these ideas I will foreground examples of my photography practice and other practitioners’. My focus is on research that explores place-based topics in which photography plays the role of generating thinking and place-making. The article positions photography as a complete practice-led research methodology within the academy, contextualising key historical practices and moments in order to propose an expanded model of place representation. I will trace the advancements of photography and its uses during the colonial period, the introduction to landscape and later the progression into tourism photography. As a counter approach to these frameworks, I propose a more nuanced iterative model of place representation capable of rendering multiple place imaginaries. This allows visual artists, practice-led researchers and ethnographers to expand existing research agendas and methodological approaches to place and place-making.